Measurements and analysis of vibrations at Virilla Bridge, national route N° 1 - Francisco Navarro-Henríquez Daniel Ureña-Muñoz (Instituto Tecnológico de Costa Rica, 2018)
This article presents the experience generated during the detailed inspection of the superstructure at the Virilla bridge, National Route N° 1, as part of the research project “eBridge 2.0: integrated bridge system performance”, by request of the National Roads Authority (CONAVI) and based on the existing inter-contract between CONAVI and the Technological Institute of Costa Rica (TEC). In this paper an overview of the bridge main features is described with an initial inspection of the structure is performed and also it is provided an analytical model of the bridge for structural analysis. The measurements allowed quantifying the vibration magnitudes and deformation in various sections of the bridge, on condition of vehicular traffic service (environmental performance). The experimental results are compared with computational analytical modeling of the structure and also with national and international standards.